2015
DOI: 10.1103/physrevb.91.125427
|View full text |Cite
|
Sign up to set email alerts
|

Exciton diffusion, end quenching, and exciton-exciton annihilation in individual air-suspended carbon nanotubes

Abstract: Luminescence properties of carbon nanotubes are strongly affected by exciton diffusion, which plays an important role in various nonradiative decay processes. Here we perform photoluminescence microscopy on hundreds of individual air-suspended carbon nanotubes to elucidate the interplay between exciton diffusion, end quenching, and exciton-exciton annihilation processes. A model derived from random-walk theory as well as Monte Carlo simulations are utilized to analyze nanotube length dependence and excitation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
160
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(171 citation statements)
references
References 65 publications
10
160
1
Order By: Relevance
“…Next, we perform PL excitation (PLE) spectroscopy [ Fig. 1(c)] to identify the chirality (n, m) = (11, 7) by comparing the E 11 and E 22 wavelengths to tabulated data [29]. Polarization dependence of PL intensity is then measured to determine the angle of the nanotube [inset of Fig.…”
Section: Photoluminescence Spectroscopy and Time-resolved Measurementioning
confidence: 99%
See 2 more Smart Citations
“…Next, we perform PL excitation (PLE) spectroscopy [ Fig. 1(c)] to identify the chirality (n, m) = (11, 7) by comparing the E 11 and E 22 wavelengths to tabulated data [29]. Polarization dependence of PL intensity is then measured to determine the angle of the nanotube [inset of Fig.…”
Section: Photoluminescence Spectroscopy and Time-resolved Measurementioning
confidence: 99%
“…It turns out that the dark-to-bright conversion efficiency depends strongly on the suspended length. We select (9,8) CNTs with lengths ranging from 0.5 to 4.2 µm and measure PL decay curves with E 22 excitation at a low power so that the effects of exciton-exciton annihilation can be negligible [29]. The influence of excitation and detection wavelengths as well as the excitation power dependence on the decay dynamics are discussed in the Supplemental Materials [28].…”
Section: Diffusion-limited Conversion Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Time-resolved transient absorption (TA) and PL spectroscopy measurements have revealed that multiple exciton states show rapid decays due to nonradiative Auger recombination. [16][17][18][19] Nonradiative Auger recombination, which competes with exciton diffusion, determines the PL efficiency of semiconducting SWCNTs, [20][21][22][23][24] and it ensures nonclassical PL by preventing the occupation of identical exciton states. 25 Carrier doping is one of the most important techniques in semiconductors, which controls their electrical and optical properties.…”
mentioning
confidence: 99%
“…Despite the fact that SWCNTs have long been used as saturable absorbers [12,13] due to their large nonlinear absorption [14,15], the strong nonlinear photoluminescence (PL) has been modeled only considering a reduction in quantum efficiency due to exciton-exciton interactions and not nonlinear optical absorption due to BGR. The presence of BGR would call into question the basic understanding high fluence SWCNT PL saturation experiments [6,8,16] and the consequently extracted SWCNT properties [5,17]. BGR has been previously observed in several one-dimensional systems.…”
Section: Introductionmentioning
confidence: 99%